2004
DOI: 10.1128/iai.72.2.782-787.2004
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Statherin Peptide-Binding Epitopes of Commensal and Potentially Infectious Actinomyces spp. Delineated by a Hybrid Peptide Construct

Abstract: Adhesion of microorganisms to host receptor molecules such as salivary statherin molecules is a common event in oral microbial colonization. Here we used a hybrid peptide construct (with both a hydroxyapatitebinding portion and a test peptide portion) to map the interaction of Actinomyces species (and Candida albicans) with statherin. Adhesion to hybrid peptides and truncated statherin variants revealed three binding types, types I to III. (i) Type I strains of rat, hamster, and human infection origins bound C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…In addition, the adhesion of P. gingivalis fimbriae (Amano et al, 1996a) and the cells of Actinomyces spp. (Niemi & Johansson, 2004) was not affected by statherin in solution. Domains of statherin involved in interaction with F. nucleatum are also thought to be cryptic.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In addition, the adhesion of P. gingivalis fimbriae (Amano et al, 1996a) and the cells of Actinomyces spp. (Niemi & Johansson, 2004) was not affected by statherin in solution. Domains of statherin involved in interaction with F. nucleatum are also thought to be cryptic.…”
Section: Discussionmentioning
confidence: 82%
“…2). Several reports have suggested that binding sites of salivary proteins including statherin and PRP1 in oral bacteria might be cryptic Amano et al, 1996a;Kataoka et al, 1997;Niemi & Johansson, 2004). PRP1, in solution, showed no inhibitory effect on adhesion of Streptococcus gordonii cells and P. gingivalis fimbriae (Kataoka et al, 1997) to PRP 1-coated HAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a significant affinity for calcium phosphate precipitates, including hydroxyapatite, and is present as an enamel pellicle protein within the oral cavity (5). Statherin also contains sites for the adhesion of bacteria such as Porphyromonas gingivalis and Streptococcus mutans to the tooth surface (6,7), and these sites are thought to be a feature that the microorganisms have exploited for biofilm development (8). Therefore, it would be significant to determine whether FDC-SP has a similar activity to statherin.…”
Section: Fdc-spmentioning
confidence: 99%
“…STATH plays a key role in the development of the oral cavity biofilm by mediating adhesion of bacteria and was recently identified as being the most prominent protein in the saliva-air interface (31). It is known to have bacterial binding epitopes that promote the growth and adhesion in the oral cavity of some organisms (Porphyromonas gingivalis and Fusobacterium nucleatum) while inhibiting the growth of others (Peptostreptococci and S. aureus) (14,32,33). Its antimicrobial effect on P. aeruginosa has not been investigated.…”
Section: Mild Versus Severe Cf Differential Gene Expressionmentioning
confidence: 99%